2007
DOI: 10.33997/j.afs.2007.20.3.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Body Shape and Food Habits of Fish from Three Reservoirs of Sri Lanka

Abstract: In the present paper, an attempt is made to investigate whether the body shape indices can be used to predict food habits of fish species in three reservoir fish communities of Sri Lanka. The present analysis is based on the studies on food and feeding habits of fish species and their body shape indices in three Sri Lankan reservoirs, namely Minneriya, Udawalawe and Victoria. Body proportions of individual fish species were determined as P1 (= Maximum height of the body/ Maximum width of the body) and P2 (= To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Fish species were classified based on depth or water column use as follows: surface dwellers, mid-column dwellers, or bottom dwellers (Lowe-McConnell 1975, 1987Arunachalam 2000;Bhat 2002). Fishes' feeding preferences were categorized as phytophagous (algivore, herbivore, and detritivore), heterotrophic (insectivore and carnivore), or omnivorous (Arunachalam 2000;Bhat 2002;Weliange and Amarsinghe 2007;Johnson and Arunachalam 2012;Froese and Pauly 2016). The flow responses of fish species were classified as eurytopic, limnophilic, or rheophilic (Aarts and Nienhuis 2003;Chakrabarty and Homechaudhuri 2013).…”
Section: Guild-based Classification Of Fish Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fish species were classified based on depth or water column use as follows: surface dwellers, mid-column dwellers, or bottom dwellers (Lowe-McConnell 1975, 1987Arunachalam 2000;Bhat 2002). Fishes' feeding preferences were categorized as phytophagous (algivore, herbivore, and detritivore), heterotrophic (insectivore and carnivore), or omnivorous (Arunachalam 2000;Bhat 2002;Weliange and Amarsinghe 2007;Johnson and Arunachalam 2012;Froese and Pauly 2016). The flow responses of fish species were classified as eurytopic, limnophilic, or rheophilic (Aarts and Nienhuis 2003;Chakrabarty and Homechaudhuri 2013).…”
Section: Guild-based Classification Of Fish Speciesmentioning
confidence: 99%
“…Earlier studies on fish diversity have described functional responses of fish guilds to riverine habitat gradients or stream characteristics (De Silva et al. ; Bhat ; Weliange and Amarsinghe ; Johnson and Arunachalam ; Oliveira et al. ; Chakrabarty and Homechaudhuri ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The study of body morphology in relation to feeding ecology in fish species was pioneered by Keast and Webb in 1966 at a small Canadian lake [37,38]. Subsequently, Catella and Petrere (1998) reported that body shapes of fish species from a floodplain lake in Brazil were related to their feeding habits [27].…”
Section: Effects Of Feeding Habits On Fish Body Shapementioning
confidence: 99%
“…Food activities of fish occur by stim- ulation (Lall & Tibbets, 2009;Nanjo et al, 2008) that arises due to the color and smell of food (Weliange & Amarasinghe, 2007). In addition, fish are interested in moving objects in the water.…”
Section: Diet Compositionmentioning
confidence: 99%